Spatial variation in bacterial community in natural wetland‐river‐sea ecosystems. (13th April 2017) - Zhang, Hongxia; Zheng, Shiling; Ding, Jiawang; Wang, Oumei; Liu, Fanghua
Abstract : Wetland‐estuarine‐marine environments are typical oxic/anoxic transition zones and have complex water flow‐paths within the zone of mixing where freshwater interacts with ocean water. Little is known about the impact of this interaction on bacterial community structures or the relationship between bacterial community and geochemical factors in such transitional mixing environments. Hence, we investigated the distribution patterns and diversity in bacterial communities in the Yellow River estuary‐coastal wetland‐Bohai Sea transition zone by analyzing 39 samples from 13 ordered sites. High‐throughput sequencing of the 16S rRNA gene revealed significant shifts in diversity and distribution of bacterial community in sediments from the Yellow River estuary to the Bohai Sea. Yellow River sediment was dominated by hydrogen‐, nitrogen‐, and iron‐cycling bacteria, such as Hydrogenophaga, Nitrospira, Pseudomonas, and Thiobacillus . The coastal wetland had a haloduric community associated with different functions, such as Planctomyces, Marinobacter, Halomonas, Salinivibrio, and Salinibacter . The Bohai Sea sediment had a higher relative abundance of Lutimonas, Desulfococcus, Photobacterium, Propionigenium, and Vibrio . Spatial variation in bacterial community was correlated with pH, salinity and sulfate ( S O 4 2 − ) concentration in such coastal environments. The major bacterial taxa were significantly different across the wetland, estuary, and coastal marine ecosystems, indicating substantial spatial heterogeneity among the three ecosystems. Statistical analysis revealed strong links between variation in bacterial community structure and ecosystem type. Our results demonstrate the importance of geographic and geochemical factors in structuring the bacterial community in natural environments.